Effects of adjective use of melatonin and vitamin C in the treatment of chronic periodontitis: A randomized clinical trial - Mohammadtaghi Chitsazi; Masoumeh Faramarzie; Mehrnoosh Sadighi; Adileh Shirmohammadi; Arash Hashemzadeh (Tabriz University of Medical Sciences, 2017)
Background. Melatonin can eliminate free radicals and this function can be intensified byvitamin C. Melatonin and vitamin C can have synergic antioxidant effects. The aim of thisstudy was to investigate the effects of adjunctive use of melatonin and vitamin C in the non-surgical treatment of chronic periodontitis. Methods. Sixty subjects with chronic periodontitis were included in this study and randomly allocated to three groups: group 1) 20 patients received non-surgical periodontal treatment; group 2) 20 patients received non-surgical periodontal treatment with adjunctive use of melatonin; and group3) 20 patients received non-surgical periodontal treatment with combination use of melatonin + vitamin C. Clinical parameters (PD, CAL,GI) were recorded at baseline and at 3-month and 6-month intervalsafter treatment. Data were analyzed with paired t-test, one-way ANOVA andrepeated-measures ANOVA. A significant difference was assumed at P<0.05. Results. Non-surgical periodontal therapy improved PD and CAL 3 and 6 months treatment compared to baseline (P<0.001). There was a significant improvement in PD and CAL scores at 6-month interval compared to 3 months in the melatonin+ vitamin C group (P<0.05), while the differences in PD and CAL scores between the mentioned intervals were not significant between the control and melatonin groups (P>0.05). Therefore adjunctive dose of vitamin C offered an additional effect at this interval. Conclusion. Combination therapy with melatonin and vitamin C can improve the results of non-surgical periodontal therapy.